Perubahan Fonologis Protobahasa Minangkabau dalam Isolek Koto Tinggi - Husni Mardhyatur Rahmi; Nadra Nadra; Reniwati Reniwati (Universitas Mulawarman, 2023)
This study describes the types of phonological changes that occur from the Minangkabau protolanguage in an isolect of Koto Tinggi. The research is conducted by applying listening and speaking methods, as well as recording and note-taking techniques in the process of providing data. Triangulation techniques are used to test the validity of the data. Furthermore, the data are analyzed by using a top-down reconstruction approach and an articulatory phonetic method. After being compared, the data are grouped based on the types of sound changes. The data analysis results are presented descriptively using formal and informal methods. The result shows that Minangkabau protolanguage undergoes phonological changes in the isolect of Koto Tinggi in the form of (1) lenition; (2) fortition; (3) dissimilation; (4) sound loss, which includes apheresis, syncope, apocope, and haplology; (5) sound addition, namely prothesis and paragoge; and (6) diphthongization process. Phonological changes do not occur in all sounds and are incomplete in all positions.